Field guide to fishes of the Mekong Delta (Mekong River Coomission, 2008)
The main purpose of this book to service as a practical guide for technicians, students and other researchers of fish in the water bodies of the Mekong Delta. This book is value as a field guide to 363 of the most common fish species found in the Mekong Delta in Cambodia and Vietnam.